Guardians of the Herd: Molecular Surveillance of Tick Vectors Uncovers Theileriosis Perils in Large Ruminants - Muhammad Sohail Sajid; Asif Iqbal; Hafiz Muhammad Rizwan; Asma Kausar; Urfa Bin Tahir; Muhammad Younus; Mahvish Maqbool; Rao Muhammad Siddique; Dalia Fouad; Farid Shokry Ataya (Microorganisms, 2023)
Theileria sp. (Piroplasmida: Theileriidae) is one of the most widely known infections transmitted by hard ticks (Acari: Ixodidae) and has been linked to significant economic losses across the globe. The study’s main emphasis was theileriosis, a disease that is common in Pakistan and has an incidence ranging from 0.6% to 33%. Through DNA screening of the vector ticks and host blood, this study sought to determine the risk of tick-borne theileriosis in populations of buffalos (Bubalus bubalis) and cattle (Bos indicus) in Toba Tek Singh district of Punjab, Pakistan. Identified tick species include Hyalomma anatolicum (35.4%), Rhipicephalus (Boophilus) microplus (30.2%), and R. sanguineus (25%). Tick specimens were collected from animals and their respective microenvironments. PCR assays targeting Theileria annulata were used to investigate the infection in the DNA extracted from the collected blood samples from large ruminants and salivary glands (SGs) of the Hyalomma ticks. The 18S rRNA of T. annulata was amplified using specific primers. Positive T. annulata amplicons were sequenced and verified using BLAST analysis. Overall, 50% of SGs contained T. annulate DNA. Female ticks, and those collected from cattle and from riverine environments had significantly higher (p < 0.05) rates of Theileria infection in their acini. Overall prevalence of Theileria infection was 35.9% in blood collected from large ruminants. Cattle had a substantially greater frequency of bovine theileriosis (43.2%) than buffalos (28.7%). Age and sex of large ruminants were significantly positively associated (p < 0.05) with Theileria infection. Furthermore, compared to non-riverine cattle (35%) and buffalo (19.5%), riverine cattle (52.2%) and buffalo (36.2%) showed a considerably higher prevalence. The results of this study, which is the first in Pakistan to examine the blood of large ruminants and vectorial function of Ixodid ticks in the transmission of T. annulata along with associated risk factors, offer an important insight for risk assessment of Theileria infection in livestock using vectorial infectivity.